Improving the nutritional profile of jelly candies - Melissa Filipini da Silveira; Prof. Dr. Priscilla Efraim; Maria Júlia Viscondi Silva; Júlia das Neves de Aro; Ana Lúcia Fadini; Guilherme de Castilho Queiroz; Flávio Martins Montenegro; Marise Bonifácio Queiroz (Applied Food Research, 2025)
A Central Composite Rotatable Design (CCRD) was used to evaluate the influence of adding orange juice and a fiber: polyol mix (1:1) on the moisture content, water activity, and texture of starch jellies. Based on the results of CCRD, a sample was selected for a stability study over 180 days at 25 °C (Diet Fruit - DF), along with two sugar-added control samples (Regular Fruit – RF; Regular - R). The nutritional facts and front of pack labeling were made according to the Brazilian and European Regulations. The coefficient of determination (R2) and the Fcalculated resulted in first-order models for hardness and stickiness responses. The addition of orange juice above 11.5 % reduced hardness and stickiness of the candies. Concentrations above 38.3 % of fiber: polyol mix reduced the hardness, with less influence on stickiness. Major changes in the jellies occurred between 0 and 90 days, primarily with a reduction in moisture and an increase in hardness, adhesiveness, and stickiness. The DF sample, which contained a higher amount of juice, presented a higher content of total phenolic and antioxidant capacity, was characterized as a source of fiber, did not require the “high added sugar” front-of-pack label, and received a Nutri-Score B, indicating an improvement in the nutritional profile.